Global Financial Architecture after the Crisis (Economic and Political Thought, 2011)
The article aims to present the existing global financial architecture againsta background of global architecture and directions of necessary reforms inthe context of global economy protection against the global financial and economic crises.The future global financial architecture on the one hand should be basedon broader legitimization and on the other hand should provide highereffectiveness of preventing and fighting with crises.The main reason for the failures of the present global financial architecturein this field is its inability to keep up with the development of globalizationprocesses that are a source of global macroeconomic imbalance as well as newrisks for stability of the global financial system. It is necessary to introducechanges of the liberalizing and regulating global financial architecture intoa model of coordinated market economy – also on a global scale. In thenew architecture, a bigger role should be played by the countries with thehighest economic potential: the so called emerging markets such as China,India, Brazil, etc. The reforms that are being implemented in the globalfinancial institutions – the IMF and the World Bank – are going exactly in this direction.Moreover, it is necessary to consider the development of a global financialinstitution sharing both liberalizing and regulating powers. The institutionshould condition financial liberalization on accepting the adopted adequateregulatory solutions by the member states.